Efektivitas Pemberian Dispensasi Kawin dalam Menekan Angka Pernikahan di bawah Umur Selama Masa Pandemi COVID- 19 di Pengadilan Agama Magetan - Ananda Yuliana Putri; Sutrisno Sutrisno (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2022)
The impact of the COVID-19 pandemic, which has not yet ended, has now penetrated all sectors, in addition to having an impact on the health, economy and tourism sectors, the COVID-19 pandemic also has an impact on the increasing number of underage marriages. Underage marriages can certainly cause various problems due to the incompetence of the prospective bride and groom, which has an impact on the number of applications for marriage dispensation, one of which occurs at the Magetan Religious Court. In Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, underage marriage is allowed if it receives a marriage dispensation from the Religious Court. The purpose of this study is to find out about the implementation of the marriage dispensation both before and after the COVID-19 pandemic, and also the judges' considerations in granting or refusing a marriage dispensation. This research is empirical juridical type. The analytical method used is qualitative with the resulting data in the form of descriptive analysis, in this study the authors obtained data by means of interviews, literature study, and observation. The results of the study found that there were differences in the provision of marriage dispensations before and after the COVID-19 pandemic, where there was a significant increase in requests for marriage dispensations caused by certain factors that will be explained in this study